If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -59 + 23 = -2x + 11x Combine like terms: -59 + 23 = -36 -36 = -2x + 11x Combine like terms: -2x + 11x = 9x -36 = 9x Solving -36 = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -36 + -9x = 9x + -9x Combine like terms: 9x + -9x = 0 -36 + -9x = 0 Add '36' to each side of the equation. -36 + 36 + -9x = 0 + 36 Combine like terms: -36 + 36 = 0 0 + -9x = 0 + 36 -9x = 0 + 36 Combine like terms: 0 + 36 = 36 -9x = 36 Divide each side by '-9'. x = -4 Simplifying x = -4
| 3z=51 | | 4(2-2n)+8=-6-(3n+8) | | 12u^3+20u^2-48u=0 | | 9x+10+3x-4=180 | | (4x-8)-(7x-9)= | | (64u^6v^12)^1/3 | | (7/24)/(1/6) | | 8(v+3)-2v=2(3v+4)-13 | | 2x^2-2x-6=x^2-x-4 | | f+8squared=3squared | | x-13x=3x-6 | | 36=12x+x^2 | | y=-x+6x-12 | | a(5)=6 | | 3+11x-1=9x+29-7x | | 4.9x-10x/3-12 | | 12x=9x+342 | | 8x+19=6x+34 | | 5x^2+17x-17=3-4x | | (14x^7-16x^3)/2x^3 | | x+(x*.22)=275 | | 4X+43=2X+69 | | (2*x-10/3)*(5/6*x-30) | | (2x-10/3)x(5/6x-30) | | 26x=64 | | (3v-7)(5-v)=0 | | (7x^2+2)(4x^2-19x-5)=0 | | 5k-10/12/6k | | 4(5x-4)+6=-4 | | 4h=220m | | (2x+3)(3x^2-13x+12)=0 | | y=6-2/3y |